Characterizing riverbed sediment using high‐frequency acoustics: 1. Spectral properties of scattering. Issue 12 (19th December 2014) - Buscombe, D.; Grams, P. E.; Kaplinski, M. A.
Abstract Bed sediment classification using high‐frequency hydroacoustic instruments is challenging when sediments are spatially heterogeneous, which is often the case in rivers. The use of acoustic backscatter to classify sediments is an attractive alternative to analysis of topography because it is potentially sensitive to grain scale roughness. Here a new method is presented which uses high‐frequency acoustic backscatter from multibeam sonar to classify heterogeneous riverbed sediments by type (sand, gravel, and rock) continuously in space and at small spatial resolution. In this, the first of a pair of papers that examine the scattering signatures from a heterogeneous riverbed, methods are presented to construct spatially explicit maps of spectral properties from georeferenced point clouds of geometrically and radiometrically corrected echoes. Backscatter power spectra are computed to produce scale and amplitude metrics that collectively characterize the length scales of stochastic measures of riverbed scattering, termed "stochastic geometries." Backscatter aggregated over small spatial scales have spectra that obey a power law. This apparently self‐affine behavior could instead arise from morphological scale and grain scale roughnesses over multiple overlapping scales or riverbed scattering being transitional between Rayleigh and geometric regimes. Relationships exist between stochastic geometries of backscatter and areas of rough and smooth sediments. However, no one parameter can uniquely characterize a particular substrate nor definitively separate the relative contributions of roughness and acoustic impedance (hardness). Combinations of spectral quantities do, however, have the potential to delineate riverbed sediment patchiness, in a data‐driven approach comparing backscatter with bed sediment observations (which is the subject of part two of this manuscript).